The Influence of Financial Knowledge and Financial Attitudes on Financial Management Behavior on UMKM Actors in Lahomi Sub-District - Daeli, Dimensi; F. Hulu, Perlindungan; Bu’ulolo, Nanny A.; Bate’e, Maria Magdalena (Manunggal Halim Jaya, 2024)
This research aims to determine the influence of financial knowledge and financial attitudes towards financial management behavior among MSMEs in Lahomi sub-district. This research is included in associative research. This result of the research shows that (1) there is a positive and significant influence of financial knowledge on financial management behavior among MSMEs in Lahomi District (2) there is a positive and significant influence of financial attitudes on financial management behavior among MSMs in Lahomi District (3) there is a positive and not significant influence on the financial management behavior of MSMEs in Lahomi District.